Ecological Systems Theory - Yang, Eunhwa; Sanborn, Bonnie (A Handbook of Theories on Designing Alignment Between People and the Office Environment, 2021)
This chapter provides background on ecological systems theory (EST) as a set of dynamic interactions and interdependencies in five layered systems - micro-, meso-, exo-, macro-, and chrono-systems - and the applicability of EST in workplace studies. What happens in the workplace can be best understood in nested systems beyond a single setting to which individuals are subject; this is the essence of applying EST. Subtopics are categorized into five areas of study in this chapter: workplace flexibility, work-family relationships, individual vitality, workplace and organizational vitality, and community vitality. EST-inspired workplace research includes qualitative, theoretical exploration, and empirical studies using interviews, surveys, observation, and controlled experiments. There are three main research gaps: (1) methodological limitation, (2) lack of integration of multiple levels, and (3) exclusion of built environments. Limitations of applying EST to workplace studies lie in the complexity of dissecting interwoven relationships among different systems. A holistic understanding of environmental changes beyond the workplace, however, allows us to see the relationships between the workplace and other dimensions of life and highlights the importance of the workplace environment.